MENINGKATKAN PROSES DAN HASIL BELAJAR MATEMATIKA MELALUI PENDEKATAN KONTEKSTUAL MODEL CTL KELAS IV SD - M. SYAFEI (Pengurus Pusat Perkumpulan Masyarakat Peduli Pendidikan, 2014)
In general, the learning activities in school teachers still use a less conventional approach to actively involve students so that students feel tired and bored , learning is seen to be an alternative to overcome these problems is to adopt ,